Pengaruh Husnudzon Dengan Afirmasi Positif Dalam Menurunkan Tingkat Stres Akademik Siswa Unggulan Kelas 12 SMA Wachid Hasyim 1 Surabaya - Syahdiantary, Indah; Yazid, Syaifulloh; Aziza, Syifa Nur Fatimatul (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
The background of this study is based on the phenomenon of stress that often occurs among students and has a negative impact on the well-being of students, namely academic stress. The results of the initial interview showed that some excellent students had experienced stress due to academic pressure, competition with peers, and pessimism about their own abilities. As a treatment effort, it is used with Cognitive restructuring techniques applied through the husnudzon approach (good prejudices) with positive affirmations. The purpose of this study was to determine the effect of husnudzon with positive affirmations in reducing academic stress in excellent students. The type of research is quantitative with experimental design one group pre-test and post test, and involved 12 students of Class XII were selected through purposive sampling technique. The instrument used was the Sarafino and Smith academic stress scale. The Data were analyzed using Paired Sample t-Test to measure differences in students ' academic stress levels before and after treatment. The results of statistical analysis showed that the average score of academic stress decreased from 95.75 (pretest) to 76.17 (posttest). Paired samples t-test obtained the value of Sig. (2-tailed) by 0.000 (p < 0.05), which indicates a significant difference between before and after the intervention. Thus, the alternative hypothesis (Ha) is accepted which means husnudzon with positive affirmations has an effect on reducing the level of academic stress in Class XII superior students at SMA Wachid Hasyim 1 Surabaya.